Phytochemicals in Bifunctional Roles: From Defense Molecules in Plants to Therapeutic Agents in Humans - Pathak, Niti; Tiku, Anupama Razdan (Pharmacognosy Reviews)
Medicinal plants have gained a lot of interest in the recent past as healing components in the primary health care system. They possess a multitude property due to the presence of bioactive compounds which include alkaloids, phytosterols, flavonoids, saponins, terpenoids, dietary f ibers, peptides, etc. in varied dosages and in different parts of the plant. These phytochemicals are produced by plants for their defense but are extracted by users for their antimicrobial and healing properties. Knowledge about the usage of plant parts in curing ailment and health promotion has been passed orally through indigenous communities for ages. However, in nature, overexploitation of resources has led to the depletion of medicinal plants of high therapeutic value. Introduction of plant tissue culture, metabolic engineering, and other modern techniques have shown mass-scale production of these plants with high concentrations of bioactive components. Thus, an amalgamation of information gathered from local communities along with large-scale production of secondary metabolites through traditional and modern techniques and their utilization in disease treatment is the basis for good health.
Keywords: Bioactive compounds; Traditional techniques; Plant tissue culture techniques; Metabolic Engineering